Estudio y análisis de los de movimientos en masa en el barrio "9 de diciembre", perteneciente al cantón Celica de la provincia de Loja, como base para su ordenamiento territorial. - Atarihuana Sandoval, Celso Xavier (2009)
The present investigation is the result of field work and analysis developed in the neighborhood out December 9 City Celica, Loja Province. This research contains a general characterization of geodynamic processes in the area of study, made on the basis of field observations, the inventory of mass movements, the laboratory analysis of soil and waste sector surveys of residents across the neighborhood, to obtain in this way the conclusions and recommendations that the case warrants. The city of Celica, head of the parish Celica Canton is located in the south-western province of Loja in southern Ecuador. This city belongs to the district 9 th December, which is our study area. This district covers an area of approximately 3.74 hectares, located in an area of outstanding medium-high, with heights ranging from 1971 m to 1987 m. All the study area lies on soil residual product of a high degree of weathering of volcano-sedimentary rocks with interbedded lavas Keel Unit, which mainly residual soils and human activities as factors conditioning and water as a trigger factor have generated two mass movement processes within the Barrio 9 December, affecting homes, schools and civil infrastructure. The field work has helped define these two types of unstable areas in the study area, thus taking the presence of a translational type movement and a slow movement or soil creep. To characterize these processes was necessary to prepare base maps and topographic, geological and hydrological pending. Translational slippage covers an area of 31535,6 m2; the soil type is clay, with a slope between 15° and 20°. The district covers 50% of the total area of this landslide. While the slow movement or creep of soil covers an area of 10219,4 m2; the soil type is clay, covered by a layer between 30 cm and 50 cm of organic soil, with a slope of between 35° and 25°. These geodynamic processes, are the threats, risks, physical vulnerability and socio-economic, which determine the susceptibility or the occurrence of mass movements that arise in the neighborhood 9th of December. It is vital that their interpretation and representation, as we allow the development of land management plan for the study area. The implementation of immediate and mediate actions and referential budgets are covered by this research, mentioning the responsibility of both the general population and the Municipality of Celica in particular implement these prevention measures as part of a Risk Management System.